Social resistance to LGBT intersubjectivity: A sociocultural analysis from Jambi, Indonesia - Al Munir, M. Ied (Jurnal Anifa: Studi Gender dan Anak, 2025)
This article analyzes social resistance to LGBT intersubjectivity within the sociocultural context of Jambi, Indonesia, by examining divergent epistemological constructions of truth. Using a qualitative field-based research design, the study was conducted in Jambi City and involved in-depth interviews with religious leaders, traditional leaders, and health professionals as key social actors. Data were analyzed through data condensation, data display, and conclusion drawing, and interpreted using an epistemological framework. The findings reveal two main insights. First, LGBT individuals articulate their identities and lived experiences through an intersubjective understanding of truth, grounded in shared meanings and collective experiences. Second, this intersubjective framework encounters social resistance manifested through three dominant sociocultural perspectives: religious perspectives grounded in subjective truth, medical perspectives emphasizing objective truth, and customary perspectives that also operate within an intersubjective understanding of truth. These differing epistemological positions shape how the Jambi community interprets and responds to LGBT presence. This study contributes to LGBT studies and sociocultural theory by demonstrating how competing constructions of truth underpin social resistance in local contexts. It highlights the importance of epistemological awareness in understanding social tensions surrounding sexual and gender diversity in culturally plural societies.